OPTIMALISASI BEBAN KERJA DAN PENENTUAN URUTAN KERJA DALAM MENINGKATKAN EFISIENSI SISTEM OPERASI - Saniah Lidiya Hawani; Dionisius Sihombing; Fatimah Azzahra Saragih; Helda Anggraini; Rahma Alya; Ahmad Rusdi Pasya Hasibuan (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2026)
Operational inefficiency is often caused by uneven workload distribution and unplanned job sequencing. Both factors lead to bottlenecks, prolonged waiting times, and ineffective resource utilization. This study investigates how workload optimization and sequencing decisions contribute to improving operating system efficiency. Using a descriptive literature study approach based on secondary data from sources on organizational behavior and operations management, the findings indicate that workload imbalance causes bottlenecks and declining workforce performance, while unstructured sequencing prolongs makespan and increases idle time. Priority rules such as Shortest Processing Time and Earliest Due Date can demonstrably shorten total completion time while improving resource utilization, whereas workload equalization has been shown to reduce operational disruptions. This study finds that addressing both variables simultaneously produces greater efficiency gains than handling them separately. Practitioners are advised to periodically assess workload distribution and apply sequencing methods suited to their respective production characteristics.